Moderate-to-vigorous physical activity attenuates the detrimental effects of television viewing on the cardiorespiratory fitness in Asian adolescents: the Asia-fit study - Tetsuhiro Kidokoro; Koya Suzuki; Hisashi Naito; Govindasamy Balasekaran; Jong Kook Song; Soo Yeon Park; Yiing Mei Liou; Dajiang Lu; Bee Koon Poh; Kallaya Kijboonchoo; Stanley Sai-chuen Hui (BMC, 2019)
Abstract Background Moderate-to-vigorous physical activity (MVPA) and television viewing are independently associated with cardiorespiratory fitness. However, limited evidence is available on their combined effects, specifically of MVPA and watching television, on cardiorespiratory fitness in the young Asian population. Therefore, the present study examined whether MVPA can attenuate the detrimental effects of prolonged television viewing on the cardiorespiratory fitness of Asian adolescents. Methods This is a cross-sectional study on 9553 adolescents (aged 12-15 years) from 8 Asian metropolitan cities (Tokyo, Hong Kong, Shanghai, Taipei, Bangkok, Kuala Lumpur, Seoul, and Singapore). Cardiorespiratory fitness was assessed by using a 15-m progressive aerobic capacity endurance run (PACER) test. The time spent on MVPA and watching television was assessed using the International Physical Activity Questionnaire-Short Form. Results MVPA was more closely associated with the PACER score than the duration of watching television. Compared with the reference group (i.e. those with the lowest levels of MVPA [< 30 min/day] and the most sedentary [≥3 h/day of television time]), PACER scores were significantly higher for those who met the physical activity recommendation (≥60 min/day in MVPA), regardless of the duration of television viewing. Conversely, girls in the least active group (< 30 min/day of MVPA) who watched television < 1 h/day demonstrated better PACER scores than the reference group. Conclusions Sufficient MVPA (≥60 min/day) can attenuate the detrimental effects of excessive television viewing with cardiorespiratory fitness in Asian adolescents. In addition, the duration of television viewing had significant but weaker associations with cardiorespiratory fitness compared to MVPA.